Pengaruh Servicescape, Lokasi Dan Promosi Terhadap Keputusan Pembelian Pada Café Richeese Factory Rantauprapat - Riko Firnanda Silalahi; Mulya Rafika; Abd Halim (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the effect of servicescape, location and promotion on purchasing decisions at Café Richeese Factory Rantauprapat. The research method used in this research is quantitative. In this study, the population is Café Richeese Factory Rantauprapat consumers as much as unknown. The research sample uses incidental sampling technique is a sampling technique based on chance, that is, anyone who happens to meet the researcher can be used as a sample, if it is deemed that the person who happened to be met is suitable as a data source. This study uses non-probability sampling techniques because the population is unknown, and with purposive sampling as the sampling technique. Because the population of members is not known with certainty, the sample size is calculated using the Cochran formula with a research sample of 96 people. The data collection techniques used are observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The results of the study prove that Servicescape has a positive and significant effect on Purchasing Decisions at Café Richeese Factory Rantauprapat. Location has a positive and significant effect on Purchasing Decisions at Café Richeese Factory Rantauprapat. Promotion has a positive and significant effect on Purchasing Decisions at Café Richeese Factory Rantauprapat. Servicescape, Location and Promotion simultaneously have a positive and significant effect on Purchasing Decisions at Café Richeese Factory Rantauprapat. The coefficient of determination of 0.346 means that the Purchasing Decision can be explained by the Servicescape (X1), Location (X2) and Promotion (X3) variables by 34.6%, while the remaining 65.4% can be explained by other variables not examined in this study. Keywords: Servicescape, Location, Promotion, Purchase Decision